Sidney and Harriet Janis Collection. - Palais des beaux-arts Bruxelles; Barr, Alfred H. Jr.; van Lerberghe, Jan (Brussel : Paleis voor Schone Kunsten Brussel, 1971)
Albers, Josef ; Anuskiewicz, Richard ; Arp, Hans (Jean) ; Bellmer, Hans ; Boccioni, Umberto ; Brauner, Victor ; De Chirico, Giorgio ; Dali, Salvador ; Delaunay, Robert ; Dine, Jim ; van Doesburg, Theo ; Doriani, William ; Dubuffet, Jean ; Duchamp, Marcel ; Eilshemius, Louis Michael ; Ernst, Max ; Fahlström, Öyvind ; Giacometti, Alberto ; Gorky, Arshile ; Herbin, Auguste ; Hirshfield, Morris ; Jawlensky, Alexej von ; Johns, Jasper ; Kandinsky, Wassily ; Kane, John ; Kelly, Ellsworth ; Klee, Paul ; Kline, Franz ; de Kooning, Willem ; Leger, Fernand ; Lichtenstein, Roy ; Lissitzky, El ; MacDonald-Wright, Stanton ; Magritte, René ; Marisol ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Mondriaan, Piet ; Oldenburg, Claes ; Picasso, Pablo ; Pollock, Jackson ; Rosenquist, James ; Rothko, Mark ; Schwitters, Kurt ; Segal, George ; Steinberg, Saul ; Still, Clyfford ; Sullivan, Patrick J. ; Tobey, Mark ; Torres Garcia, Joaquin ; Vasarely, Victor ; Vivin, Louis ; Warhol, Andy ; Wesselmann, Tom
biografie
Sidney and Harriet Janis Collection, Palais des Beaux-Arts, Bruxelles, 7 Janvier - 11 Fevrier 1971
Frans
boek